2020
DOI: 10.2147/ott.s272869
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functional Implication of Exosomal miR-217 and miR-23b-3p in the Progression of Prostate Cancer</p>

Abstract: Objective The microRNA expression profile of plasma exosomes in prostate cancer (PCa) is of critical importance in the disease exploration. This study aimed to explore the clinical application of exosomal miRNAs as biomarkers for PCa. Methods Exosome-like vesicles of PCa patients and healthy controls were purified by differential centrifugation. The purified vesicles within the ranges of 50 and 100 nm were classified as exosomes according to the results of transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In the present study, miRNAs upstream of NCAPG were predicted via bioinformatics analysis, and miR-23b-3p was selected as the candidate miRNA. miR-23b-3p is known to be an important modulator of cellular physiology, and has been strongly associated with cancer development ( 14 ); In fact, the expression levels of miR-23b-3p were reported to be downregulated in cervical ( 25 ), lung ( 26 ) and prostate cancer ( 27 ). Consistent with the results of these aforementioned studies, the findings of the current study revealed that miR-23b-3p expression was downregulated in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miRNAs upstream of NCAPG were predicted via bioinformatics analysis, and miR-23b-3p was selected as the candidate miRNA. miR-23b-3p is known to be an important modulator of cellular physiology, and has been strongly associated with cancer development ( 14 ); In fact, the expression levels of miR-23b-3p were reported to be downregulated in cervical ( 25 ), lung ( 26 ) and prostate cancer ( 27 ). Consistent with the results of these aforementioned studies, the findings of the current study revealed that miR-23b-3p expression was downregulated in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-217 encapsulated in exosomes exerts roles in promoting tumor cell proliferation, invasion, and EMT. 324 MiR-1246, a tumor inhibitor, was downregulated in PCa cell-derived exosomes. Overexpression of exosomal miR-1246 inhibits tumor cell proliferation, migration, and invasion and promoted cell apoptosis by suppressing EMT.…”
Section: The Roles Of Exosomal Ncrnas In Human Diseasesmentioning
confidence: 95%
“…Prostate antigen has been the most widely used biomarker, however exosomal miR-NAs have been recently proposed to distinguish aggressive from nonaggressive prostate cancers, guide treatment, and predict prognosis of disease (Lorenc et al, 2020). For instance, miR-217 and miR-23b-3p have been implicated in proliferation and invasion of prostate cancer, suggesting that they can be used as potential biomarkers and therapeutic targets in prostate cancer (C. Zhou et al, 2020).…”
Section: Exosomes As Diagnostic Markers In Cancermentioning
confidence: 99%